Spanish-Israeli relations and systemic pressures, 1956-1986: The cases of GATT, NATO and the EEC - Setton, Guy; Rein, Raanan (Historia y Política, 2018)
Based on the Constructivist theoretical approach for analyzing international relations by identifying the forces which influence states behavior, this article compares major junctions in Spain’s international status and the way systemic changes influenced the course of Spanish-Israeli relations. The article looks at Madrid’s entry into the international trade regime represented by the General Agreement on Tariffs and Trade (GATT) in 1963, Spain’s joining the Council of Europe in 1977, Madrid’s inclusion in NATO in 1982, and its entry into the European Economic Community (EEC) in 1986. We argue that this last milestone left Madrid with little option but to establish relations with Israel. This proved that systemic pressure, derived from Spain’s new status in the EEC, was crucial for the establishment of bilateral diplomatic ties.